Sediment-associated heavy metal contamination and potential ecological risk along an urban river in South Africa - Chaka Mohajane; Munyaradzi Manjoro (Heliyon, 2022)
Sediment contamination by heavy metals poses one of the worst environmental risks to aquatic ecosystems worldwide. The study explored sediment-associated heavy metal contamination and potential ecological risk along the Molopo River in Mahikeng, South Africa. Total concentrations of arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb), and zinc (Zn) were analysed using inductively coupled plasma mass spectrometry. Various indices were applied to assess the level of contamination and ecological risk. Most heavy metal concentrations at selected upstream and downstream sites were below average shale, except Cr, Cu, Hg, Pb, and Zn. The contamination factor (CF) indicates that the level of contamination was low (CF < 1) at most sampling sites, except Cr, Cu, Pb and Zn, which varied from moderate (1 CF < 3) to considerable (3 ≤ CF < 6) contamination. The enrichment factor (EF) shows that Cd, Cr, Cu, and Zn were moderate (2 EF < 5) to significantly enriched (5 EF < 20) at the affected sites. The results suggest anthropogenic enrichment (EF > 2) of Cd, Cr, Cu, and Zn. The threshold effect concentration and probable effect concentration sediment quality guidelines predicted that Cr, Cu, and Ni concentrations were more likely to have harmful effects on bottom-dwelling organisms. Pearson correlation and principal component analysis reveal that Cd, Cr, Cu, Ni, Pb, and Zn had a common anthropogenic source. We attribute the source to industrial and wastewater effluent, vehicle traffic, and runoff from various urban surfaces in the city. The study provides baseline data for heavy metal monitoring in the study area. Future research and monitoring should focus on heavy metals that cause concern because of their concentrations (Cr, Cu, Pb, and Zn) and potential ecological risk (Cr, Cu, and Ni).